Representasi Nilai Maskulinitas Tokoh Minke Dalam Film Bumi Manusia Garapan Sutradara Hanung Bramantyo - Karlina, Rini; Syihabbudin, Syihabbudin (Jurnal Ilmiah Wahana Pendidikan, 2024)
Masculinity is always explained as values that can build a male identity in society and also as a barrier to values that are not feminine. So, masculinity has become a very important topic regarding gender. This research aims to describe the masculinity found in the character Minke in the film Bumi Manusia. The film Bumi Manusia is a film by director Hanung Bramantyo based on a romance by Pramoedya Ananta Toer which tells the story of the struggle of the Indonesian people against Dutch colonialism in 1899, the end of the 19th century and the beginning of the 20th century. This research is a qualitative descriptive research method. The data in this research are dialogues or conversations that contain masculinity found in the character Minke in the film Bumi Manusia. Meanwhile, the data source in this research is the film Bumi Manusia which was written in the form of a dialogue script. Data collection techniques were carried out using listening and note-taking techniques. The results of this research show that the masculinity in the film Bumi Manusia is found in the main character Minke. The characteristics of masculinity found in the film Bumi Manusia include the image of a man in his appearance, leadership, strength, courage and determination within him. However, the more dominant characteristic of masculinity found in the film Bumi Manusia is the character of determination possessed by the male characters.